1998
DOI: 10.1108/01443589810233658
|View full text |Cite
|
Sign up to set email alerts
|

Testing for monetary policy convergence in European countries

Abstract: The paper tests for long-run monetary policy convergence and short-run policy interactions in seven ERM countries over the 1979-1992 period using the approach of multivariate cointegration and Granger-causality tests. We provide evidence for very little monetary policy convergence, even during the more stable 1987-1992 period. Our tests for short-run monetary policy interactions show that, in agreement with some other studies, Germany is not the leader country in the system as it appears to accommodate shocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Multilateral convergence tests deal with a separate issue as they can be used to test for the degree of convergence among the interest rates of all the EMS member countries Hafer and Kutan (1994). andBredin and Fountas (1996) follow this approach.…”
mentioning
confidence: 99%
“…Multilateral convergence tests deal with a separate issue as they can be used to test for the degree of convergence among the interest rates of all the EMS member countries Hafer and Kutan (1994). andBredin and Fountas (1996) follow this approach.…”
mentioning
confidence: 99%
“…Hafer et al (1997) find partial convergence of term structures in four large European countries from 1979 through 1995. Partial convergence of inflation rates and long-term interest rates for various subset of EU countries were reported by, e.g., Katsimbris and Miller (1993), Hafer and Kutan (1994), Bredin and Fountas (1998), Holmes (1998), and Phengpis et al (2004). Evidence of partial convergence in industrial production and GDP growth during the 1990s were found by Bernard and Durlauf (1995), Serletis and Krichel (1992), Mills and Holmes (1999), and Holmes (2002).…”
Section: Introductionmentioning
confidence: 90%